KEBERMAKNAAN HIDUP PADA PEKERJA SEKS KOMERSIAL (PSK) YANG TERINFEKSI HIV/AIDS DI KOTA BANDUNG - Dimas Isnain Widyawan; Erwin Fazrin; Cahyaning Widhyastuti (LPPM UNIBI, 2021)
The meaning of life is the appreciation of the individual in finding something valuable or important for the individual himself. Meaningless living conditions are often faced by sex workers who are infected with HIV/AIDS because of discrimination and stigma that they get from society. This study aims to provide an overview of the meaning of life, the process of achieving and the factors that influence the meaningfulness of life for sex workers who infected by HIV/AIDS. This study uses a qualitative method with a case study approach. The sample in this study were 2 sex workers infected with HIV/AIDS in Bandung. The data were collected by using in depth interview and observation that held for two times. The data were analized using the descriptive analysis technique. Based on the data obtained, the results show that the two subjects basically have unique ways and patterns in interpreting their lives. Both can find the meaning of their respective lives. The first subject interprets his life to establish household relationships and raise his children while the second subject interprets his life in a way that is useful for the environment, especially his family. This is influenced by relationships with the environment and family, appreciation of the profession and appreciation of love.